Secondary particle silicon carbon material as well as preparation method and application thereof
By forming secondary particle silicon carbon materials, combining porous carbon and nano-silicon, the problem of insufficient expansion and magnification performance of existing silicon carbon materials is solved, and the effect of low expansion and high magnification is achieved, which is suitable for lithium-ion secondary batteries.
Patent Information
- Application Number
- CN202411640801.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The single-particle structure of existing gas-phase silicon carbon materials leads to large expansion and contraction, and the long lithium ion transmission path, which limits its application in terminal products, especially in terms of energy density and cycling performance.
Using secondary particle silicon carbon material, materials with low expansion and high magnification properties are prepared by melting spherical primary particles and forming secondary particles, combining porous carbon and nano-silicon, and porous structures are formed by pyrolytic carbonization and activation treatment. , and nanosilicon is deposited through silane compounds, and finally carbon coating is carried out.
It effectively reduces the charging volume expansion of silicon-carbon materials, improves the rate performance, and significantly improves the electrochemical performance. It is suitable for industrial production and the application of lithium-ion secondary batteries.
Smart Images

Figure CN119170786A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and in particular to a secondary particle silicon-carbon material and a preparation method and application thereof. Background Art
[0002] With the development of consumer electronics, new energy vehicles and electric aircraft, the market demand for high energy density electrode materials is becoming more and more urgent. Silicon material has a theoretical capacity of up to 4200mA·h / g, and can be alloyed to form Li 15 Si4, its gram capacity can reach 3579mA·h / g. Therefore, the application of silicon materials to the negative electrode of the battery is conducive to greatly improving the energy density of the battery. The silicon inside the gas phase silicon carbon can be evenly distributed in the porous carbon in the form of dispersed small particles, and the electrochemical performance is significantly improved, which has great development potential.
[0003] However, the existing gas-phase silicon-carbon materials are all single-particle structures. The expansion and contraction of a single particle during charging and discharging are large, and the lithium ion transmission path is long. The potential for further improvement in expansion and rate performance is limited, which limits their application in terminal products.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] One of the purposes of the present invention is to provide a secondary particle silicon-carbon material having the characteristics of low expansion and high rate, which solves the technical problems of low energy density and poor cycle performance of silicon-carbon negative electrode materials in the prior art.
[0006] The second object of the present invention is to provide a method for preparing secondary particle silicon-carbon material, which has a simple process, high efficiency, high success rate and is suitable for industrial production.
[0007] The third object of the present invention is to provide an application of a secondary particle silicon-carbon material, which can effectively reduce the expansion of lithium-ion secondary batteries, effectively improve their rate performance, and achieve outstanding application effects.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: In a first aspect, a secondary particle silicon-carbon material comprises porous carbon and nano-silicon dispersed on the porous carbon; The porous carbon includes porous carbon formed by secondary particles; The D50 particle size of the secondary particles is 3 μm to 15 μm; The secondary particles are formed by the fusion of spherical primary particles; The particle size of the primary particles is 20% to 50% of the particle size of the secondary particles.
[0009] Furthermore, the average sphericity of the primary particles is 0.6 to 1.0; The D50 particle size of the primary particles is 0.6 μm to 7.5 μm.
[0010] Furthermore, the specific surface area of the secondary particle silicon-carbon material is not higher than 5m 2 / g.
[0011] Furthermore, the resistivity of the secondary particle silicon-carbon material is 10 mΩ·cm~1000 mΩ·cm.
[0012] Furthermore, the grain size of the nano-silicon is below 2 nm.
[0013] In a second aspect, a method for preparing the secondary particle silicon-carbon material described in any one of the above items comprises the following steps: The secondary particle hard carbon precursor is first subjected to pyrolysis and carbonization, and then subjected to activation treatment to obtain porous carbon, and the porous carbon is subjected to nano-silicon deposition to obtain the secondary particle silicon-carbon material.
[0014] Furthermore, the method for preparing the secondary particle hard carbon precursor comprises the following steps: The carbon source is polymerized to generate primary particles, and the primary particles are then fused to obtain the secondary particle hard carbon precursor; The carbon source comprises at least one of glucose, fructose, galactose, lactose, sucrose, maltose, rice starch, mung bean starch, wheat starch, cassava starch, corn starch, cellulose and phenolic resin; The additives used in the polymerization reaction include at least one of maleic anhydride, hydroxymethyl cellulose, sodium hexametaphosphate, sodium lauryl sulfate, polyvinyl alcohol, hexadecyltrimethylammonium bromide and polyvinyl pyrrolidone; The amount of the additive is 0.01% to 0.5% of the weight of the carbon source; The polymerization reaction temperature is 150°C to 350°C; The polymerization reaction pressure is 2Mpa~8Mpa.
[0015] Furthermore, the temperature of the pyrolysis carbonization is 800°C to 1400°C, and the time of the pyrolysis carbonization is 1h to 12h; The activation treatment method includes at least one of a physical activation method and a chemical activation method; The gas used in the physical activation method includes at least one of water vapor, air and carbon dioxide.
[0016] Furthermore, the nano-silicon deposition method includes thermal decomposition deposition through silane compounds; The temperature of the pyrolysis deposition is 300°C to 800°C, and the time of the pyrolysis deposition is 1h to 12h; After the nano-silicon deposition, the step of coating the obtained silicon-carbon material is also included; The coating process includes carbon coating process.
[0017] In a third aspect, a use of the secondary particle silicon-carbon material described in any one of the above items in a lithium-ion secondary battery.
[0018] Compared with the prior art, the present invention has at least the following beneficial effects: The secondary particle silicon-carbon material provided by the present invention, the porous carbon is formed by secondary particles, and the secondary particles are formed by the fusion of spherical primary particles. Since the expansion of the primary particles in the secondary particles is isotropic, they will restrict the expansion of each other, thereby reflecting that the expansion of the apparent single secondary particles will be reduced. In addition, there are gaps between the particles, so the overall expansion of the silicon-carbon material will be significantly reduced; at the same time, since the contact area between the secondary particles and the electrolyte is large and the transmission path of lithium ions is short, the rate performance of the silicon-carbon material can be improved; in addition, the spherical particle morphology of the primary particles is more conducive to the formation of a dense and uniform SEI film, thereby further improving the electrochemical properties of the silicon-carbon material; in short, with the coordinated cooperation of primary particles, secondary particles and their specific particle sizes, the silicon-carbon material of the present invention effectively reduces the charging volume expansion, while improving the rate performance, and has the characteristics of low expansion and high rate.
[0019] The method for preparing the secondary particle silicon-carbon material provided by the present invention has simple process, high efficiency, high success rate and is suitable for industrial production.
[0020] The application of the secondary particle silicon-carbon material provided by the present invention can effectively reduce the expansion of lithium-ion secondary batteries, effectively improve their rate performance, and achieve outstanding application effects. BRIEF DESCRIPTION OF THE DRAWINGS In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 A 10,000-fold scanning electron microscope image of the secondary particle silicon-carbon material provided in Example 1 of the present invention; Figure 2 A 20,000-fold scanning electron microscope image of the secondary particle silicon-carbon material provided in Example 1 of the present invention; Figure 3The first charge and discharge curve of the lithium button battery of the secondary particle silicon-carbon material obtained in Example 1 of the present invention; Figure 4 This is a dQ / dV curve of the first charge and discharge of a lithium button cell made of secondary particle silicon-carbon material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0022] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] According to a first aspect of the present invention, there is provided a secondary particle silicon-carbon material, comprising porous carbon and nano-silicon dispersed on the porous carbon; The porous carbon includes porous carbon formed by secondary particles, and the D50 particle size of the secondary particles can be 3 μm to 15 μm, and its typical but non-limiting D50 particle size is, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, and 15 μm; The secondary particles are formed by the fusion of spherical primary particles. The particle size of the primary particles can be 20% to 50% of the particle size of the secondary particles, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, but not limited thereto.
[0024] The secondary particle silicon-carbon material provided by the present invention, the porous carbon is formed by secondary particles, and the secondary particles are formed by the fusion of spherical primary particles. Since the expansion of the primary particles in the secondary particles is isotropic, they will restrict the expansion of each other, thereby reflecting that the apparent expansion of a single secondary particle will be reduced. In addition, there are gaps between the particles, so the overall expansion of the silicon-carbon material will be significantly reduced; at the same time, since the contact area between the secondary particles and the electrolyte is large and the transmission path of lithium ions is short, the rate performance of the silicon-carbon material can be improved; in addition, the spherical particle morphology of the primary particles is more conducive to the formation of a dense and uniform SEI film, thereby further improving the electrochemical properties of the silicon-carbon material.
[0025] In summary, with the coordinated cooperation of primary particles, secondary particles and their specific particle sizes, the silicon-carbon material of the present invention effectively reduces the charging volume expansion, while improving the rate performance, and has the characteristics of low expansion and high rate.
[0026] In a preferred embodiment, the average sphericity of the primary particles may be 0.6-1.0, and typical but non-limiting average sphericity is, for example, 0.6, 0.7, 0.8, 0.9, and 1.0, which can further form a dense and uniform SEI film.
[0027] In the present invention, the D50 particle size of the primary particles can be 0.6μm~7.5μm, for example, 0.6μm, 0.8μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, but is not limited to this.
[0028] It should be noted that if the particle size of the primary particles is too small, the surface area will be too large, resulting in more side reactions, which will reduce the initial effect and storage properties of the silicon-carbon material. At the same time, the connections between the primary particles are thin, and the particles are easy to fall off and fail after expansion; if the particle size of the primary particles is too large, it will be difficult to form a secondary particle granulation structure, which is not conducive to improving the expansion and rate properties of the silicon-carbon material.
[0029] In a preferred embodiment, the specific surface area of the secondary particle silicon carbon material is not more than 5m 2 / g, for example, 5m 2 / g, 4m 2 / g, 3m 2 / g, 2m 2 / g, 1m 2 / g, but is not limited to this.
[0030] The average particle size D50 of the secondary particles, the average particle size D50 of the primary particles and the specific surface area selected by the present invention, under the action of various specific parameters, can further reduce the charging volume expansion of the silicon-carbon material and further improve the rate performance of the silicon-carbon material.
[0031] In a preferred embodiment, the resistivity of the secondary particle silicon-carbon material of the present invention can be 10mΩ·cm~1000mΩ·cm, and its typical but non-limiting resistivity is, for example, 10mΩ·cm, 30mΩ·cm, 50mΩ·cm, 100mΩ·cm, 200mΩ·cm, 300mΩ·cm, 400mΩ·cm, 500mΩ·cm, 600mΩ·cm, 700mΩ·cm, 800mΩ·cm, 900mΩ·cm, and 1000mΩ·cm.
[0032] In a preferred embodiment, the grain size of nano silicon can be below 2 nm, for example, 2 nm, 1.8 nm, 1.6 nm, 1.4 nm, 1.2 nm, 1 nm, 0.5 nm, but not limited to this. The smaller grain size of nano silicon is more conducive to reducing the charging volume expansion and is more conducive to improving the first reversible capacity and the first efficiency.
[0033] In the present invention, the proportion of nano-silicon in the silicon-carbon material can be 10wt%~90wt%, and its typical but non-limiting proportions are, for example, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, and 90wt%. The appropriate proportion of nano-silicon is more conducive to making the silicon-carbon material have the characteristics of low expansion and high initial efficiency; if the proportion of nano-silicon is too low, the capacity and initial efficiency of the material will be lower; if the proportion of nano-silicon is too high, the structural stability of the material will be poor and the expansion will be higher.
[0034] According to a second aspect of the present invention, there is provided a method for preparing the secondary particle silicon-carbon material as described in any one of the above, comprising the following steps: The secondary particle hard carbon precursor is first subjected to pyrolysis and carbonization, and then subjected to activation treatment to obtain porous carbon, and nano-silicon deposition is performed on the porous carbon to obtain a secondary particle silicon-carbon material.
[0035] The method for preparing the secondary particle silicon-carbon material provided by the present invention has simple process, high efficiency, high success rate and is suitable for industrial production.
[0036] In a preferred embodiment, the method for preparing the secondary particle hard carbon precursor comprises the following steps: The carbon source is polymerized to generate primary particles, which are then fused together to obtain secondary particles of hard carbon precursor.
[0037] In the present invention, the method for preparing the secondary particle hard carbon precursor comprises the following steps: The carbon source, additives and water are mixed and reacted to polymerize the carbon source. During the polymerization reaction, primary particles with a particle size of 0.6μm~7.5μm are first generated. The incompletely solidified primary particles will collide with each other under stirring, and the particles will fuse to obtain secondary particles of hard carbon precursor. In a preferred embodiment, the carbon source includes but is not limited to at least one of glucose, fructose, galactose, lactose, sucrose, maltose, rice starch, mung bean starch, wheat starch, tapioca starch, corn starch, cellulose and phenolic resin.
[0038] In a preferred embodiment, the additives include but are not limited to at least one of maleic anhydride, hydroxymethyl cellulose, sodium hexametaphosphate, sodium dodecyl sulfate, polyvinyl alcohol, hexadecyltrimethylammonium bromide and polyvinyl pyrrolidone. The additives can regulate the particle size of the primary particles through electrostatic repulsion and steric hindrance, and then merge into the desired secondary particles.
[0039] In the present invention, the amount of the additive can be 0.01%~0.5% of the weight of the carbon source, for example, it can be 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, but not limited to this. The appropriate amount of the additive is more conducive to improving the formation effect of primary particles and secondary particles of a specific particle size; if the amount of the additive is too small, the configuration of the secondary particles cannot be effectively formed; if the amount of the additive is too much, the particle size of the primary particles formed is too small, which will result in a lower primary efficiency of the material.
[0040] In a preferred embodiment, the polymerization reaction temperature can be 150°C ~ 350°C, and typical but non-limiting temperatures are, for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 325°C, 350°C; the polymerization reaction pressure can be 2Mpa ~ 8Mpa, and typical but non-limiting pressures are, for example, 2Mpa, 3Mpa, 4Mpa, 5Mpa, 6Mpa, 7Mpa, 8Mpa.
[0041] Appropriate temperature and pressure of the polymerization reaction are more conducive to further improving the formation effect of secondary particles and spherical morphology; if the temperature and / or pressure of the polymerization reaction is too low, the supercritical state cannot be formed, resulting in difficulty in conducting the polymerization reaction; if the temperature and / or pressure of the polymerization reaction is too high, the polymerization reaction rate will be too fast, resulting in only a single particle structure being formed, and it is difficult to form a secondary particle structure.
[0042] In a preferred embodiment, the temperature of pyrolysis carbonization can be 800°C ~ 1400°C, and typical but non-limiting temperatures are, for example, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, and 1400°C; the time of pyrolysis carbonization can be 1h ~ 12h, and typical but non-limiting times are, for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, and 12h.
[0043] The appropriate temperature and time of pyrolysis carbonization are more conducive to improving the formation effect of porous carbon materials; if the temperature of pyrolysis carbonization is too high and / or the time is too long, the resulting structure will be too dense, resulting in difficulty in subsequent activation and pore formation; if the temperature of pyrolysis carbonization is too low and / or the time is too short, the active groups will not be completely removed, resulting in more side reactions in the battery.
[0044] In a preferred embodiment, the activation treatment method can be at least one of a physical activation method and a chemical activation method; wherein the gas used in the physical activation method includes but is not limited to at least one of water vapor, air and carbon dioxide, which is more conducive to further improving the effect of the activation treatment.
[0045] In the present invention, the method of depositing nano-silicon includes but is not limited to thermal decomposition deposition by silane compounds.
[0046] In a preferred embodiment, the temperature of the pyrolysis deposition can be 300°C to 800°C, and typical but non-limiting temperatures are, for example, 300°C, 400°C, 500°C, 600°C, 700°C, and 800°C; the time of the pyrolysis deposition is 1h to 12h, and typical but non-limiting times are, for example, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, and 12h.
[0047] In the present invention, after the nano-silicon deposition, the step of coating the obtained silicon-carbon material is also included; wherein the coating treatment includes but is not limited to carbon coating treatment, and the carbon coating treatment can be performed by a carbon source gas.
[0048] A typical preparation method of a secondary particle silicon-carbon material comprises the following steps: (a) mixing a carbon source, an additive and water to polymerize the carbon source, generating primary particles with a particle size of 0.6 μm to 7.5 μm during the polymerization reaction, and then fusing the primary particles to obtain secondary particles of hard carbon precursor; (b) pyrolyzing and carbonizing the secondary particle hard carbon precursor of step (a) to obtain secondary particle hard carbon, i.e., porous carbon precursor; (c) activating the porous carbon precursor of step (b) to obtain a secondary particle porous carbon material; (d) The porous carbon material of step (c) is sequentially adsorbed with a silane compound (nano-silicon deposition raw material) and a carbon source gas (carbon coating raw material) for pyrolysis treatment to obtain a secondary particle silicon-carbon material.
[0049] According to a third aspect of the present invention, there is provided a use of the secondary particle silicon-carbon material described in any one of the above items in a lithium-ion secondary battery.
[0050] The application of the secondary particle silicon-carbon material provided by the present invention can effectively reduce the expansion of lithium-ion secondary batteries, effectively improve their rate performance, and achieve outstanding application effects.
[0051] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0052] Example 1 A method for preparing a secondary particle silicon-carbon material comprises the following steps: S1: 20 kg sucrose (carbon source), 40 g polyvinyl alcohol (additive) and 100 kg pure water were mixed in a high-pressure reactor and polymerized at 180 ° C for 2 hours. During the polymerization process, primary particles were generated first, and the incompletely solidified primary particles collided with each other under stirring, and the particles merged to obtain secondary particles of hard carbon precursor; S2: The secondary particle hard carbon precursor is first subjected to high temperature carbonization at 900°C for 4 hours in a nitrogen atmosphere, and then subjected to air flow pulverization to obtain secondary particle hard carbon, i.e., porous carbon precursor; S3: introducing carbon dioxide into the porous carbon precursor in a rotary kiln for high temperature activation at 900°C for 12 hours to obtain a secondary particle porous carbon material; S4: Pyrolyzing the secondary particle porous carbon material and monosilane in a CVD furnace at 500°C for 4h to deposit nano-silicon in the pore structure of the porous carbon to obtain a silicon-carbon precursor; Afterwards, acetylene was introduced at 550° C. for 2 h to coat the silicon-carbon precursor, thereby obtaining a secondary particle silicon-carbon material.
[0053] The physical and chemical parameters of the secondary particle silicon-carbon material obtained in this embodiment are shown in Table 1, and its 10,000-fold scanning electron microscope image is shown in Figure 1 , 20000 times scanning electron microscope image see Figure 2 .
[0054] Example 2 The difference between this embodiment and embodiment 1 is that in step S1, sucrose is replaced with glucose; The remaining steps and their parameters are as in Example 1 to obtain secondary particle silicon-carbon material. The physical and chemical index parameters are shown in Table 1.
[0055] Example 3 The difference between this embodiment and embodiment 1 is that in step S1, polyvinyl alcohol is replaced with sodium lauryl sulfate; The remaining steps and their parameters are as in Example 1 to obtain secondary particle silicon-carbon material. The physical and chemical index parameters are shown in Table 1.
[0056] Example 4 The difference between this embodiment and embodiment 1 is that in step S1, sucrose is replaced with corn starch; The remaining steps and their parameters are as in Example 1 to obtain secondary particle silicon-carbon material. The physical and chemical index parameters are shown in Table 1.
[0057] Example 5 The difference between this embodiment and embodiment 1 is that in step S2, the carbonization temperature is 1100°C; The remaining steps and their parameters are as in Example 1 to obtain secondary particle silicon-carbon material. The physical and chemical index parameters are shown in Table 1.
[0058] Example 6 The difference between this embodiment and embodiment 1 is that in step S3, carbon dioxide is replaced with water vapor; The remaining steps and their parameters are as in Example 1 to obtain secondary particle silicon-carbon material. The physical and chemical index parameters are shown in Table 1.
[0059] Example 7 The difference between this embodiment and embodiment 1 is that in step S1, sucrose is replaced by cellulose, polyvinyl alcohol is replaced by maleic anhydride, and the amount of maleic anhydride added is 20 g; The remaining steps and their parameters are as in Example 1 to obtain secondary particle silicon-carbon material. The physical and chemical index parameters are shown in Table 1.
[0060] Example 8 The difference between this embodiment and embodiment 1 is that in step S1, sucrose is replaced by phenolic resin, polyvinyl alcohol is replaced by sodium hexametaphosphate, and the amount of sodium hexametaphosphate added is 25 g; The remaining steps and their parameters are as in Example 1 to obtain secondary particle silicon-carbon material. The physical and chemical index parameters are shown in Table 1.
[0061] Example 9 The difference between this embodiment and embodiment 1 is that in step S1, polyvinyl alcohol is replaced with polyvinyl pyrrolidone, and the amount of polyvinyl pyrrolidone added is 25 g; The remaining steps and their parameters are as in Example 1 to obtain secondary particle silicon-carbon material. The physical and chemical index parameters are shown in Table 1.
[0062] Comparative Example 1 The difference between this comparative example and Example 1 is that in step S1, polyvinyl alcohol is not added; The remaining steps and their parameters are as in Example 1 to obtain silicon-carbon material. The physical and chemical index parameters are shown in Table 1.
[0063] Compared with Example 1, in this comparative example, no secondary particle configuration can be formed because polyvinyl alcohol is not added.
[0064] Comparative Example 2 The difference between this comparative example and Example 1 is that in step S1, the amount of polyvinyl alcohol added is 400 g; The remaining steps and their parameters are as in Example 1 to obtain silicon-carbon material. The physical and chemical index parameters are shown in Table 1.
[0065] Compared with Example 1, in this comparative example, since too much polyvinyl alcohol was added, the particle size of the primary particles was 0.25 μm.
[0066] Comparative Example 3 The difference between this comparative example and Example 1 is that in step S1, the amount of polyvinyl alcohol added is 1 g; The remaining steps and their parameters are as in Example 1 to obtain silicon-carbon material. The physical and chemical index parameters are shown in Table 1.
[0067] Compared with Example 1, in this comparative example, since too little polyvinyl alcohol was added, a secondary particle configuration could not be formed.
[0068] Test Example 1 The physical and chemical parameters of the average particle size D50, average sphericity of the primary particles, and the average particle size D50, specific surface area, pore volume and particle size distribution K90 of the porous carbon obtained in each embodiment and comparative example are shown in Table 1.
[0069] The particle size (μm) range of the material was tested using Dandong Better Laser Particle Sizer BT-9300ST; The specific surface area (m² / g) of the material is tested using JW-DX dynamic adsorption specific surface area meter. Field emission scanning electron microscopy (SEM) (JSM-7800F) was used to analyze the morphology and pattern processing of the materials; The XRD diffractometer (Panalytical X'PERT PRO MPD, Netherlands) was used to analyze the phase of the material and determine the grain size of the material; The pore volume of the material was tested using the American Quantachrome Autosorb IQ3.
[0070] Table 1
[0071] It can be seen from Table 1 that the type of additives, their addition amounts, and the type of carbon source have a great influence on the particle size of the primary particles; it can be seen from the data of Examples 1, 2, and 4 that as the molecular weight of the carbon source gradually increases, the particle size of the primary particles also gradually increases; it can be seen from the data of Examples 1 and 3 that, at the same addition ratio, the particle size of the primary particles formed by using sodium dodecyl sulfate as an additive is smaller; in Comparative Example 1, since no additives were added, a secondary particle configuration could not be formed; in Comparative Example 2, since more additives were added, the particle size of the primary particles was only 0.25 μm; in Comparative Example 3, since there were fewer additives, a secondary particle configuration could not be formed.
[0072] Test Example 2 The performance of the silicon-carbon materials obtained in each embodiment and comparative example was tested, and the results are shown in Table 2.
[0073] The specific surface area (m² / g) of the material was tested using a JW-DX dynamic adsorption specific surface area meter.
[0074] Silicon-carbon material, conductive carbon black and binder are mixed in pure water at a mass ratio of 94.5:1.5:4, homogenized, and the solid content is controlled to be 48wt%, coated on a copper foil current collector, vacuum-baked at 100°C for 8h, pressed and formed, and then punched to prepare a negative electrode sheet; The button half-cell was assembled in a glove box filled with argon. The counter electrode was a metal lithium sheet, the separator used was PE, and the electrolyte was 1 mol / L LiPF6 EC / DMC (Vol 1:1). Carry out charge and discharge test on button batteries, the test process is 0.1C DC to 0.005V, 0.05C DC to0.005V, 0.02C DC to 0.005V, Rest 10min, 0.1C CC to 1.5V; The first reversible capacity and efficiency of silicon-carbon materials were measured; Among them, the button battery testing equipment is the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.
[0075] The silicon-carbon material is tested for its first reversible capacity by the above-mentioned charge-withdrawal test method, and then a certain amount of the same graphite negative electrode is mixed according to calculation, and the secondary particle silicon-carbon material is mixed to 600±5mA·h / g, abbreviated as S600; The S600 mixed material, conductive carbon black and binder (mass ratio 92:2:6) were homogenized in pure water, the solid content was controlled to 48wt%, and the mixture was coated on a current collector with a copper foil as the substrate, and then vacuum-baked at 90°C for 8h, pressed by a roller press, and then sliced by a slicing device to prepare a negative electrode sheet; the thickness of the negative electrode sheet was measured by a micrometer and recorded as T1, and the thickness of the substrate was measured as T2, and the data were recorded; Assemble button half-cells in an argon-filled glove box, with the counter electrode being a metal lithium sheet, the separator being a PE material, and the electrolyte being 1 mol / L LiPF6 EC / DMC (Vol 1:1); perform charge and discharge tests on the button cell, with the test process being 0.1CDC to 0.005V, 0.05C DC to 0.005V, 0.02C DC to 0.005V, Rest 10min, 0.1C CC to1.5V, 0.1C DC to 0.005V, 0.05C DC to 0.005V, 0.02C DC to 0.005V; measure the first reversible capacity and efficiency of the negative electrode material; The battery is disassembled, and the thickness of the negative electrode material obtained by the disassembly is detected and recorded as T3; the first full-charge expansion data of the negative electrode material is calculated according to the formula F=(T3-T1) / (T1-T2), and F is the first full-charge expansion rate; The button cell testing equipment is the LAND battery testing system of Wuhan Landian Electronics Co., Ltd.; the slicing equipment is the MSK-T10 button half-cell slicing equipment of Kejing; the micrometer detection equipment is the Japanese Mitutoyo 293-100-10; and the rolling equipment is the MSK-HRP-05 button half-cell slicing equipment of Kejing.
[0076] The silicon-carbon material powder is mixed with the graphite negative electrode (mass ratio is 10~80:20~90) to obtain a mixed negative electrode powder, and then the negative electrode powder, Super p and BP-7 are mixed in pure water at a mass ratio of 92:4:4, and the solid content is controlled at 48wt%. After slurrying, it is coated on a current collector with a copper foil as the substrate, placed in a vacuum baking oven at 80℃-100℃ for vacuum baking for 4h-8h, and the pole piece is cold pressed with a commercial roller pressing equipment of Kejing, and the pole piece is sliced into small discs with a diameter of 15mm-22mm using a commercial slicing equipment of Kejing to prepare a silicon composite negative electrode pole piece; commercial 523 positive electrode material, SP and PVDF (polyvinylidene fluoride) are mixed with an appropriate amount of NMP (N-methyl pyrrolidone) solvent, control the solid content to 55wt%, apply the mixed slurry on the current collector with aluminum foil as the substrate, place it in a vacuum oven at 90℃-120℃ for vacuum baking for 4h-8h, use Kejing commercial roller pressing equipment to cold press the pole piece, use Kejing commercial slicing equipment to slice the pole piece into small discs with a diameter of 15mm-22mm to prepare the positive pole piece; dry it at 85℃ vacuum (-0.1MPa) for 8h, weigh and calculate the weight of the active material; the separator used is PE, and the electrolyte is 1mol / L LiPF6 EC / DMC (Vol 1:1); assemble it into a CR2430 button-type full battery in a glove box; Leave the button cell at room temperature for 2h-6h, and use 0.1C to 0.005V, 0.05Cto 0.005V, 0.02C to 0.005V, 0.1C to 1.5V, 0.2C to 0.005V, 0.2C to 1.5V, 0.5C to0.005V, 0.5C to 1.5V, 1C to 0.005V, 0.5C to 1.5V, 2C to 0.005V, and 0.5C to 1.5V to perform charge and discharge on the Blue Electric test system, and then calculate the capacity at different charge rates: rate retention rate = charge capacity at different rates / first charge capacity.
[0077] Table 2
[0078] The first charge and discharge curve of the lithium button battery of the secondary particle silicon-carbon material obtained in Example 1 is shown in Figure 3 The first charge and discharge dQ / dV curve of the lithium button battery of the secondary particle silicon-carbon material obtained in Example 1 is shown in Figure 4 .
[0079] It can be seen from Table 2 that the secondary particle silicon-carbon material obtained in the embodiment of the present invention has a higher first reversible capacity and a higher rate retention rate. In the lithium-ion battery test system, the first reversible capacity can reach more than 1850 mA·h / g, the first efficiency can reach more than 92%, the S600 first expansion rate is less than 34%, and the charging rate 2C / 0.1C can also reach more than 94%; the single-particle silicon-carbon material obtained in Comparative Example 1 and Comparative Example 3 has a larger expansion and a lower rate. The main reason is that the main particles are larger and there is no secondary particle structure; the silicon-carbon material with a secondary particle configuration obtained in Comparative Example 2 has a lower first efficiency, mainly because the particle size of the primary particles is too small.
[0080] By comparing the data of each embodiment and the comparative example, it can be seen that the particle size and type of the primary particles have a great influence on the expansion and rate of the silicon-carbon material; from the data of Examples 1-4, it can be seen that with the increase of the primary particle size, the initial expansion rate of S600 increases significantly and the rate also decreases slightly.
[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A secondary particle silicon-carbon material, characterized in that: It comprises porous carbon and nano-silicon dispersed on the porous carbon; The porous carbon includes porous carbon formed by secondary particles; The D50 particle size of the secondary particles is 3 μm to 15 μm; The secondary particles are formed by the fusion of spherical primary particles; The particle size of the primary particles is 20% to 50% of the particle size of the secondary particles.
2. The secondary particle silicon-carbon material according to claim 1, characterized in that: The average sphericity of the primary particles is 0.6 to 1.0; The D50 particle size of the primary particles is 0.6 μm to 7.5 μm.
3. The secondary particle silicon-carbon material according to claim 1 or 2, characterized in that: The specific surface area of the secondary particle silicon-carbon material is not more than 5m 2 / g.
4. The secondary particle silicon-carbon material according to claim 3, characterized in that: The resistivity of the secondary particle silicon-carbon material is 10 mΩ·cm to 1000 mΩ·cm.
5. The secondary particle silicon-carbon material according to claim 4, characterized in that: The grain size of the nano-silicon is below 2 nm.
6. A method for preparing the secondary particle silicon-carbon material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The secondary particle hard carbon precursor is first subjected to pyrolysis and carbonization, and then subjected to activation treatment to obtain porous carbon, and the porous carbon is subjected to nano-silicon deposition to obtain the secondary particle silicon-carbon material.
7. The method for preparing the secondary particle silicon-carbon material according to claim 6, characterized in that: The method for preparing the secondary particle hard carbon precursor comprises the following steps: The carbon source is polymerized to generate primary particles, and the primary particles are then fused to obtain the secondary particle hard carbon precursor; The carbon source comprises at least one of glucose, fructose, galactose, lactose, sucrose, maltose, rice starch, mung bean starch, wheat starch, cassava starch, corn starch, cellulose and phenolic resin; The additives used in the polymerization reaction include at least one of maleic anhydride, hydroxymethyl cellulose, sodium hexametaphosphate, sodium lauryl sulfate, polyvinyl alcohol, hexadecyltrimethylammonium bromide and polyvinyl pyrrolidone; The amount of the additive is 0.01% to 0.5% of the weight of the carbon source; The polymerization reaction temperature is 150°C to 350°C; The polymerization reaction pressure is 2Mpa~8Mpa.
8. The method for preparing the secondary particle silicon-carbon material according to claim 6, characterized in that: The temperature of the pyrolysis carbonization is 800°C to 1400°C, and the time of the pyrolysis carbonization is 1h to 12h; The activation treatment method includes at least one of a physical activation method and a chemical activation method; The gas used in the physical activation method includes at least one of water vapor, air and carbon dioxide.
9. The method for preparing the secondary particle silicon-carbon material according to any one of claims 6 to 8, characterized in that: The nano-silicon deposition method includes thermal decomposition deposition through silane compounds; The temperature of the pyrolysis deposition is 300°C to 800°C, and the time of the pyrolysis deposition is 1h to 12h; After the nano-silicon deposition, the step of coating the obtained silicon-carbon material is also included; The coating process includes carbon coating process.
10. Use of the secondary particle silicon-carbon material according to any one of claims 1 to 5 in a lithium-ion secondary battery.
Citation Information
Patent Citations
Silicon-carbon negative electrode material, preparation method and lithium ion battery
CN109713280A
Microporous carbon material for preparing highly-selective separation of propylene and propane by using starch and preparation method and application of microporous carbon material
CN110436462A
Biomass-based porous carbon material, preparation method and application of biomass-based porous carbon material in separation of 1, 3-butadiene from C4 olefin mixture
CN112499628A
Secondary particle hard carbon composite material and preparation method and application thereof
CN113903896A
Preparation method and application of secondary particle hard carbon microspheres
CN117658104A
